1200 V FS‐IGBT with electric field modulation layer to improve trade‐off between avalanche ruggedness and on‐state voltage drop. Issue 2 (1st January 2017) - Yang, Zhuo; Bian, Fangjuan; Zhu, Jing; Sun, Weifeng; Tian, Ye; Tong, Xin; Zhu, Yuanzheng; Ye, Peng
Abstract : In this Letter, a novel 1200 V FS‐ insulated gate bipolar transistors (IGBT) is proposed to improve the trade‐off between avalanche ruggedness and on‐state voltage drop. The proposed IGBT features the high doping and thin n‐layer under trench gates and we call it the electric field modulation layer (EFM layer). Under the avalanche condition, the EFM layer can form the sharp electric filed distribution in the EFM layer and the avalanche multiplication is constrained in the thin EFM layer. The difference between the holes and electrons due to the avalanche multiplication effect at the emitter side of the IGBT is minished. Therefore, the negative difference resistance in the avalanche I – V curve caused by the difference between the holes and electrons is eliminated. As a consequence, the avalanche ruggedness of the EFM‐IGBT is improved. In the on‐state, the high doping EFM layer can store the carriers and the on‐state voltage drop of the EFM‐IGBT is reduced to 1.48 V at 200 A/cm 2 . Finally, the EFM‐IGBT improves the trade‐off between avalanche ruggedness and on‐state voltage drop.